"Stories Take Your Role Away From You": Understanding the Impact on Health Care Professionals of Viewing Digital Stories of Pediatric and Adolescent/Young Adult Oncology Patients. (July 2017) - Laing, Catherine M.; Moules, Nancy J.; Estefan, Andrew; Lang, Mike
The purpose of this philosophical hermeneutic study was to understand the effects on health care providers (HCPs) of watching digital stories made by (past and present) pediatric and adolescent/young adult (AYA) oncology patients. Twelve HCPs participated in a focus group where they watched digital stories made by pediatric/AYA oncology patients and participated in a discussion related to the impact the stories had on them personally and professionally. Findings from this research revealed that HCPs found digital stories to be powerful, therapeutic, and educational tools. Health care providers described uses for digital stories ranging from education of newly diagnosed families to training of new staff. Digital stories, we conclude, can be an efficient and effective way through which to understand the patient experience, implications from which can range from more efficient patient care delivery to decision making. Recommendations for incorporating digital storytelling into healthcare delivery are offered.